The influence of neuroticism in the relation between stressful events and adult attachment - Teixeira, Rachel Coêlho Ripardo (2015)
Events in the life history of an individual such as childhood stressful events alter the strategies that guide behavior, specifically sexual strategies. Evolutionary Developmental Psychology suggests that development must be studied through the integration of various aspects, such as Attachment, Sexual strategies, and Personality. Important and stable part of psychology, personalitys factor Neuroticism reflects how people react to stress. Considering this, in the present thesis we analyzed the relationship between childhood stressful life events, neuroticism and adult attachment. We interviewed 173 people, 99 women and 74 men, aged from 18 to 45 years old (M= 29.51; SD= 7.3), that had a family income range from 1 to 3 Brazilian MW. We applied a Stressful Events Inventory, a Neuroticism Test, and an Attachment Scale. It was found an average of 16,59 of occurrence of stressful events (SD = 5.82). In addition to this high frequency, it was found that the greater the number of stressful events, the greater the perceived stress; and participants perceived the events as more stressful than expected. There were sex differences, with men experiencing more events related to violence and authority, and women, more events that are social. Women also tended to perceive all events as more stressful and to have higher Neuroticism. 42% of the sample had a secure attachment style, less than expected. Lastly, occurrence of stressful events, neuroticism, age, and income explained 46% of variance of this sample attachment style. A structural model analysis showed that neuroticism mediates the relationship between occurrence of stressful events and attachment, without the role of perception. This means that Neuroticism has a much larger role than previously credited, and its study in research on development can explain the high variation found when examining the relationship between childhood and adulthood